MicroRNAs in Gene Regulation: When the Smallest Governs It All. (2nd July 2006) - Ouellet, Dominique L.; Perron, Marjorie P.; Gobeil, Lise-Andrée; Plante, Pierre; Provost, Patrick
Abstract : Encoded by the genome of most eukaryotes examined so far, microRNAs (miRNAs) are small 21 -nucleotide (nt) noncoding RNAs (ncRNAs) derived from a biosynthetic cascade involving sequential processing steps executed by the ribonucleases (RNases) III Drosha and Dicer. Following their recent identification, miRNAs have rapidly taken the center stage as key regulators of gene expression. In this review, we will summarize our current knowledge of the miRNA biosynthetic pathway and its protein components, as well as the processes it regulates via miRNAs, which are known to exert a variety of biological functions in eukaryotes. Although the relative importance of miRNAs remains to be fully appreciated, deregulated protein expression resulting from either dysfunctional miRNA biogenesis or abnormal miRNA-based gene regulation may represent a key etiologic factor in several, as yet unidentified, diseases. Hence is our need to better understand the complexity of the basic mechanisms underlying miRNA biogenesis and function.